2022
DOI: 10.3390/ijerph19063385
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Skin Microcirculation Resulting from Vibration Therapy in Women with Cellulite

Abstract: Background: Cellulite is a cosmetic defect that affects over 80% of post-pubertal women. One of its pathomechanisms involves microvascular dysfunction. It has been suggested that vibration is a physical stimulus that may improve circulation in the skin and muscles. The aim of this study was to evaluate the effect of local vibration on cutaneous microcirculation and on eliminating the symptoms of cellulite in women. Methods: A total of 57 healthy women with at least grade 1 cellulite were recruited and divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Figure 2a shows the amounts of drug released after 6 h of the experiment. Some authors believe that the main cause of cellulite is in microcirculatory changes as in the area affected by cellulite, the blood flow is 35% lower than in the unaffected regions [1,4,44]. Thus, improving microcirculation is the mechanism of action for many cosmetic active ingredients used in cosmetic preparations [1,4].…”
Section: Evaluation Of the Permeation Profilementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2a shows the amounts of drug released after 6 h of the experiment. Some authors believe that the main cause of cellulite is in microcirculatory changes as in the area affected by cellulite, the blood flow is 35% lower than in the unaffected regions [1,4,44]. Thus, improving microcirculation is the mechanism of action for many cosmetic active ingredients used in cosmetic preparations [1,4].…”
Section: Evaluation Of the Permeation Profilementioning
confidence: 99%
“…Some authors believe that the main cause of cellulite is in microcirculatory changes as in the area affected by cellulite, the blood flow is 35% lower than in the unaffected regions [1,4,44]. Thus, improving microcirculation is the mechanism of action for many cosmetic active ingredients used in cosmetic preparations [1,4]. For this reason, the formulation was developed for topical administration, aiming for local vasodilatory action.…”
Section: Evaluation Of the Permeation Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of the stimuli are usually selected empirically or on the basis of the size of the sensory or motor reaction, hence the observation and registration of reactions occurring during and after the physical treatment. Thermovision is one of the most useful tools here, because it allows not only a one-time assessment of the effectiveness of the treatment but also allows you to track and evaluate serial treatments [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The whole-body vibration (WBV) training program is an alternative for a safe, effective, and low-cost exercise, which can present a satisfying compliance by previously sedentary patients [ 20 , 21 ]. It is generally assumed that vibration stimulates muscle spindles that responds with tonic vibration reflexes thereby enhancing muscle activity [ 21 , 22 , 23 ]. In the literature, two studies identified a significant blood flow increase in DM2 patients undergone vibration [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%